Salivary cortisol and cortisone responses to short-term psychological stress challenge in late adolescent and young women with different hyperandrogenic states. (May 2018) - Mezzullo, Marco; Fanelli, Flaminia; Di Dalmazi, Guido; Fazzini, Alessia; Ibarra-Gasparini, Daniela; Mastroroberto, Marianna; Guidi, Jenny; Morselli-Labate, Antonio Maria; Pasquali, Renato; Pagotto, Uberto; Gambineri, Alessandra
Highlights: Salivary cortisol and cortisone rise in response to stressful stimuli in hirsute and PCOS girls. Adolescents hirsute and PCOS display HPA-axis overactivity in response to stressful stimuli. HPA-axis overactivity is associated to adverse metabolic profile in hirsute and PCOS girls. Abstract: Hyperandrogenic disorders have been associated with psychological distress, reduced quality of life, anxiety and depression. The hypothalamic–pituitary–adrenal (HPA) axis plays a pivotal role in the adaptive response to stressor events. Salivary cortisol (SalF) and cortisone (SalE) testing have been proven to be useful in the evaluation of HPA-axis activity. This study investigated whether SalF and SalE responses to two putative stressor levels differed between the hyperandrogenic states in late adolescent and young women, thus measuring the HPA-axis adaptive response to acute stress events. We selected 161 drug-free females aged 16–19 years from a large population previously enrolled in a cross-sectional epidemiological study. Saliva was collected in the morning before and after two putative stressor events consisting in a self-filled questionnaire (weaker stressor) and in a structured interview plus physical examination by an endocrinologist (stronger stressor). SalF and SalE, as well as blood steroids, were assessed by liquid chromatography–tandem mass spectrometry. Subjects were subdivided into different groups according to the presence of: isolated menstrual irregularities (MI, oligo-amenorrhea; n = 22), isolated hirsutism (HIR, modified Ferriman–Gallwey score ≥ 8; n = 26), isolated hyperandrogenaemia (HT, testosterone >0.438 ng/mL; n = 14), and polycystic ovary syndrome (PCOS, MI with HIR and/or HT, n = 16). The remaining 83 apparently healthy subjects were used as controls. SalF and SalE significantly decreased after the weaker stressor, following the physiologic diurnal loss, in all the groups except for isolated HIR, where they remained unchanged (P = 0.091 and P = 0.118, respectively). In contrast, SalF and SalE remained unchanged after the stronger stressor in isolated MI, isolated HT and controls, whereas SalF increased significantly in isolated HIR (P = 0.011), and SalE increased significantly both in isolated HIR (P = 0.005) and in PCOS (P = 0.011) groups. SalF percentage variation in response to the stronger stressor was positively associated with systolic blood pressure in PCOS (P = 0.018), and both SalF and SalE percentage variations were positively associated with diastolic blood pressure in the isolated HIR group (P = 0.010 and P = 0.006, respectively). In addition, in the isolated HIR group, the SalF percentage variation was negatively associated with HDL cholesterol levels (P = 0.005). Finally, SalF and SalE percentage variations were positively associated with circulating androstenedione (P = 0.031 and P = 0.011, respectively) and DHEA (P = 0.020 and P = 0.003, respectively) in the isolated HIR group. In conclusion, this study demonstrates that hirsute and PCOS adolescent and young women are characterized by HPA-axis overactivity in response to stressful stimuli, as detectable by salivary glucocorticoid measurements. These data also indicate that the higher the HPA-axis activity, the higher the adrenal androgen output and the worse the metabolic profile.